The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.eatbeh.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Less symptomatic, but equally impaired: Clinical impairment in restricting versus binge-eating/purging subtype of anorexia nervosa

Abstract: Although those with AN-B/P displayed higher levels of core attitudinal and behavioral ED pathology than AN-R, no significant differences in ED-specific impairment were found between AN subtypes. Eating disorder-related impairment in AN was not related to the severity of underweight or purging behaviors, but was uniquely and positively associated with weight/shape concerns and binge eating frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 54 publications
3
22
1
Order By: Relevance
“…We suggest that the differences in the Y‐BOCS and YBC‐EDS scores between the three groups may reflect an overall greater severity of ED and comorbid symptoms in patients with AN‐B/P. As specified in Section 1, some studies have found that patients with AN‐B/P show greater ED‐related pathology, depression, and anxiety in comparison with patients with AN‐R and BN (Cassin & Von Ranson, ; Reas & Rø, ; Stein, Lilenfeld, Wildman, & Marcus, ).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…We suggest that the differences in the Y‐BOCS and YBC‐EDS scores between the three groups may reflect an overall greater severity of ED and comorbid symptoms in patients with AN‐B/P. As specified in Section 1, some studies have found that patients with AN‐B/P show greater ED‐related pathology, depression, and anxiety in comparison with patients with AN‐R and BN (Cassin & Von Ranson, ; Reas & Rø, ; Stein, Lilenfeld, Wildman, & Marcus, ).…”
Section: Discussioncontrasting
confidence: 94%
“…This is of importance because although patients with restrictive-type EDs (e.g., AN restrictive type) and binge-purge EDs (e.g., BN) share several important core attributes (e.g., elevated perfectionism, sensitivity to social rewards, and harm avoidance- Cassin & Von Ranson, 2005;Farstad, McGeown, & von Ranson, 2016), they nevertheless differ on other important characteristics, for example, greater impulsivity (Waxman, 2009) and emotional dysregulation (Anderson et al, 2018) in binge/purge-type EDs. Moreover, several studies (Carter et al, 2012;Lynn & Rø, 2018;Peat, Mitchell, Hoek, & Wonderlich, 2009) indicate that patients with AN binge-purge type (AN-B/P) show greater overall psychopathology as well as ED-related pathology and worse long-term outcome in comparison with patients with AN restricting type (AN-R) and BN. Nevertheless, other studies have not shown this discrepancy (Eddy et al, 2002;Kaye, Wierenga, Bailer, Simmons, & Bischoff-Grethe, 2013;Nagata, McConaha, Rao, Sokol, & Kaye, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a previous study on SCC-DBS by Lipsman et al showed the mean BMI of 5 patients with BP-AN (15.68 ± 1.70 kg/m 2 ) to be lower than that of 9 subjects with R-AN (18.26 ± 3.83 kg/m 2 ) at the 1-year follow-up (p ¼ 0.185) [14]. Indeed, patients with BP-AN exhibited higher levels of the core AN psychopathology, such as the restrained food intake, shape/weight concerns, and eating concerns as compared to subjects with R-AN [31]. Moreover, the former report greater neurocognitive impairments than the latter [32], which is consistent with our result on the significantly lower presurgical MMSE score seen in patients with BP-AN.…”
Section: Discussionmentioning
confidence: 89%
“…However, some patients also used compensatory behavior such as purging. AN binge-eating/purging has been recognized as a clinically relevant subtype, demonstrating higher levels of core ED psychopathology and more severe cognitive impairments, and therefore may cause significant sample heterogeneity (Reas and Rø 2018;Tamiya et al 2018). The authors were able to successfully generate iPSC-derived cortical neurons, with no differences in differentiation capability observed.…”
Section: Eating Disordersmentioning
confidence: 99%